Analisis Risiko Kecelakaan Kerja pada De-Pilling Machine After Autoclave Menggunakan Metode JSA dan Pengontrolan Risiko Menggunakan Metode HIRARC pada PT.XXX - Dhimas Indra Saputra; Deny Andesta (Fakultas Teknik, 2023)
PT XXX is one of the companies engaged in goods, more precisely the manufacture of fiber cement boards and wave boards. Every product that will be marketed will be packaged where the packaging is done in the De-pilling Machine after Autoclave (DMA) area. Not all DMA machines run automatically and are run by one person, there are still DMA machines that run manually, which still require the help of human labor, because when working in manual DMA the risk is great and is done by several people, so in this area risk analysis, risk identification, risk level determination, risk control and handling are needed as an effort to improve Occupational Health and Safety (K3). The method to be used is the Job Safety Analysis (JSA) method because this method focuses on identifying hazards in the work, then the hazards will be controlled by the Hazard Identification And Risk Control (HIRARC) method. From the analysis using the JSA method, 8 jobs were found to be at risk with an average risk level of Medium - High so risk control is needed for these 8 jobs. The work will be analyzed for hazards and controlled risks, the goal is to know the magnitude of the risk of work and prioritize controlling which jobs have the most significant risk and if possible, replace machines that are still manual with automatic machines to be more efficient, reduce risk and do not require many people.